Optimization of Online SKCK Services by the Intelkam Unit in Improving Public Services at Ngawi Police - Herawati, Aprilya Indah (Advances in Police Science Research Journal, 2024)
This research focuses on optimizing the Online Police Record Certificate (SKCK) service at the Ngawi Police Station to improve public services. Fast, easy and optimal SKCK services through SKCK Online are considered to increase user satisfaction with public services at the Ngawi Police. Therefore, this research aims to identify three main problems, namely the differences between SKCK Online and manual services, factors that influence SKCK Online services, and efforts to improve these services. This research uses a qualitative approach with data collection techniques such as observation, interviews and document study. The theory applied includes POAC management and organizational resources. The research results concluded that many people still choose manual SKCK because people are still blind to technology, therefore researchers recommend regular training for Online SKCK operators, improving computer infrastructure, and a Mobile SKCK socialization program. It is hoped that this can improve public services at the Ngawi Police through SKCK Online.